1985
DOI: 10.1007/bf00698291
|View full text |Cite
|
Sign up to set email alerts
|

Chronic encapsulated hematomas in the brain

Abstract: Two cases, one of a chronic encapsulated intracerebral hematoma occurring in a 43-year-old man and the other of an intracerebellar hematoma in an 8-year-old boy, are reported. In both cases CT scans revealed an encapsulated lesion containing the hematoma, but angiographic pictures were poor except for revealing a space-occupying lesion and a small vascular lesion. Both hematomas were successfully removed. Each case was associated with a thick, fibrous capsule that was found histologically to arise from an occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…In our review of the literature, 29 cases of this entity were reported. Vascular anomaly was frequently seen as a bleeding source in those cases, which included five angiographically occult AVMs, 7,19-21 six cavernous angiomas, 13,14,[16][17][18] one venous angioma, 9 and one unclassified vascular malformation. 3 No clear causes were established in the remaining cases, except for one case of metastatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, 29 cases of this entity were reported. Vascular anomaly was frequently seen as a bleeding source in those cases, which included five angiographically occult AVMs, 7,19-21 six cavernous angiomas, 13,14,[16][17][18] one venous angioma, 9 and one unclassified vascular malformation. 3 No clear causes were established in the remaining cases, except for one case of metastatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported cases of ECIH were followed up for less than several months before surgery, and only two cases including ours demonstrated expansion of the lesion with 14) Histological examinations demonstrated sinusoidal vessels in the capsule in most cases, and the two layer pattern in the capsule in nine cases. 1,3,7,11,12,14,16) Among these nine cases, sinusoidal vessels were located in the outer layer in five cases including ours, 3,11,14,16) and in the inner layer in the other four cases. 1,7,12) Thus, the clinicopathological characteristics of genuine ECIH may be summarized as the presence of a distinct fibrous capsule that may consist of two layers, sinusoidal vessels in the capsule, and expansion of the hematoma with repeated internal bleeding from the capsule.…”
Section: Discussionmentioning
confidence: 91%
“…Thirty cases of ECIH with histological evidence have been reported (Table 1). 1,[3][4][5][6][7][8][11][12][13][14][15][16][17]19) The mean age was 41.8 years old and the most frequent symptoms were headache and seizure. The male to female ratio is two to one, and the most frequent locations were the frontal, temporal, and parietal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…CEIH is a special type of intracerebral hematoma described for the first time in 1981, 10) with about 50 cases reported. [1][2][3][4][5][6][7][8][9][10][11][12]14,16,[18][19][20][21][22][23][24][25][26][27][28][29][31][32][33][34][35][36] Compared with normal intracerebral hemorrhage, CEIH is characterized by early age of onset and rare complication by hypertension, and almost all such lesions have developed beneath the cerebral cortex. 12) Headaches and seizures are the most common earliest symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…17,21,25) In about half of cases, the cause of the initial hemorrhage is malformation of a blood vessel, and in 10 cases, including the present one, the source of bleeding was cavernous angioma (Table 1). 18,19,21,22,24,27,30) Prospective study of 122 patients with intracranial cavernous angioma found the risk of hemorrhage is 2.63% per year, and the risk increases to 4.5% per year for patients with prior hemorrhage. 13) CEIH is characterized by the presence of a thick fibrotic capsule which histologically resembles the outer capsule of chronic subdural hematoma and is thought to develop by chronic progressive growth due to repeated bleeding from the new blood vessels in the capsule.…”
Section: Discussionmentioning
confidence: 99%